Ever green : saving big forests to save the planet - Reid, John W.; Lovejoy, Thomas E. (W.W. Norton & Company, 2022)
"Five stunningly large, unbroken forests remain on Earth: the Taiga, extending from the Pacific Ocean across all of Russia and far-northern Europe; the North American boreal, ranging from Alaska's Bering seacoast to Canada's Atlantic coast; the Amazon, covering almost the entirety of South America's bulge; the Congo, occupying Africa's wet equatorial middle and parts of six nations; and the island forest of New Guinea, twice the size of California. These megaforests are vital to preserving global biodiversity, thousands of cultures, and a stable climate, economist John W. Reid and celebrated biologist Thomas E. Lovejoy argue convincingly in Ever Green. Megaforests serve an essential role in decarbonizing the atmosphere, and saving them constitutes the fastest, most affordable way to start addressing our planet's most formidable ongoing crisis. Clear, provocative, and persuasive, Ever Green offers practical solutions--from supporting Indigenous forest stewards to planning smarter roads--in an inspiring call to action for the planet"--